High-achieving rural middle-school students' academic self-efficacy and attributions in relationship to gender. (3rd July 2021) - Assouline, Susan G.; Mahatmya, Duhita; Ihrig, Lori; Lane, Erin
ABSTRACT: This research investigates high-achieving, rural middle-school students' academic attributions and self-efficacy. The study sample (n = 77) included middle-school students attending schools in rural districts in a predominately rural, Midwestern state in the United States (U.S.). There was high participation in the Free and Reduced Lunch (FRL) program in the sample (average of 45.1% among the 8 participating districts). Students attending rural, under-resourced schools in the U.S. are vulnerable with respect to full academic development. We identified academic potential through the administration of a nationally standardized above-level test. Although there were no differences in the study sample's female and male students' scores in any of the four subject areas on the above-level test, there were differences for some of the psychosocial variables. A greater percentage of high-achieving males attributed both general school success and math success to ability; a greater percentage of high-achieving female students attributed general school success and math success to effort. Students in rural school districts often lack access to advanced educational opportunities, which may shape their beliefs about academic potential and self-efficacy and impact decisions regarding advanced coursework. Implications for school practitioners to foster the immediate and long-term talent development of high-achieving rural students are discussed.